Thematic clusters in the field of gas turbine thermal management: a co-word analysis during a century - Hosseini, Elaheh; Jafari, Soheil; Milani, Kimiya Taghizadeh; Miran Fashandi, Seyed Alireza; Nikolaidis, Theoklis (Regional Information Center for Science and Technology, 2022)
The research aims to visualize and analyze the co-word network and thematic clusters of the intellectual structure in gas turbine thermal management during 1919-2020. The study is applied research in terms of the purpose, which is conducted with a descriptive approach, scientometrics indicators, techniques of co-word, and social network analysis. Data analysis and visualization of the co-word network were represented by VoSViewer, SPSS, UCINet, and python Software. The top scientific products in the last century were related to engineering subject area and published by the USA country. Seven main clusters were identified for the index keywords, and 20 main clusters were recognized for the author keywords in Scopus regarding the network structure and thematic clusters based on the co-occurrences. Moreover, 38 clusters were identified based on the hierarchical clusters. The clusters, namely heat flux calculations and radiation effects, thermal performance optimization, and operational considerations, have central and major positions in this field and have more potential to maintain and develop themselves in the future. The future of Research and Development (R&D) activities in the area will be focused on novel cycles, heat map development, and Techno-Economic and Risk Analysis (TERA) by utilizing systematic approaches for the identification of heat sinks and sources, fluid modeling, and environmental considerations. In addition, the emerging contributors in the field will be advanced manufacturing and material considerations.
Keywords: Gas Turbine Thermal Management; Intellectual Structure; Co-Word Analysis; Thematic Clusters; Hierarchical Clustering; Strategic Diagram